Investigation of an Open Graded Asphalt Concrete Overlay for the Mitigation of Reflection Cracking Phenomenon - Yogesh N. Bafna (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The conventional technique of rehabilitating pavement through the application of an asphalt concrete (AC) overlay is often plagued by the issue of reflection cracking. This paper addresses the challenges associated with the reflection of pre-existing distress patterns onto newly laid AC overlays, leading to premature deterioration and a significant reduction in overlay lifespan. Laboratory investigations were conducted using open graded asphalt concrete (OGAC) as a crack relief layer, examining its performance under opening and mixed modes of displacement on Asphalt Concrete Slab Fatigue Testing Equipment. The study included an evaluation of conventional dense bituminous macadam (DBM) overlays and OGAC overlays subjected to simulated thermal as well as traffic loading, further monitoring of tensile strain and strength variation in the asphalt concrete overlay for a specific number of load cycles thermally simulated. Additionally, the cumulative decay parameters such as tensile force and stiffness modulus were computed, and decay parameters were analyzed along with overlay life. The results reveal that the implementation of an OGAC overlay effectively serves as a crack relief layer, offering a potential sustainable solution to mitigate reflection cracking in asphalt pavements